Accountability and Service Delivery in Local Governments in Uganda: A Case-Study of Bukedea District Local Government - Clement Emuge (Uganda Christian University, 2024)
The study was focused on the role of accountability in service delivery in local governments in Uganda: A case study of Bukedea district Local government. It was guided by three research objectives; to identify the effect of political accountability on service delivery in Bukedea district, to establish the effect of managerial accountability on service delivery in Bukedea district, to determine the effect of financial accountability on service delivery in Bukedea district. The study employed a cross sectional research design which was deemed fit for the research problem under investigation. Data from 60 respondents was collected and analyzed quantitatively The study found out that there are a number of accountability mechanisms which included monthly meetings, budgeting, financing community projects like water facility, health unit centres, school facility among others. It was also discovered that accountability and service delivery in Uganda especially in Bukedea district local government is faced with serious challenges which include; illiteracy, limited funds, corruption among others. The study concluded that there is a lot that needs to be done to streamline accountability in Local governments in Uganda especially in Bukedea district local government. Basing on the findings of the study, the following measures were recommended; Local governments should have clear hierarchies, based on a transparent attribution of functions and involvement of the local communities, every local government should have some freedom to organize itself institutionally, to manage its own affairs and to finance some services by itself. The basis for autonomy lies in democratic legitimacy, as only popular elections of the legislative councils ensure full accountability, the states should establish a council for the distribution of resources among localities, with the membership of commissioners, in addition to abdicating some tax-revenues to localities, Local councilors should also be responsible enough to monitor and supervise projects among the local community to alleviate poverty, they should have voice to question commissioners and local govern inspector at all the Payment they are operating.
Undergraduate Research